(untitled) (Ameghiniana, 2013)
An incomplete left humerus, belonging to Anas leucopbrys found in Middle Pleistocene sediments of S. E. Buenos Aires Province, is described. The age is based on the "aggregate" of mammals found in the same sediments. This species is now restricted in Argentina to the Subtropical Dominion and the northern sector of the Pampean Dominion. The present record indicates a more southern distribution of the species in Middle Pleistocene times.